Evaluating the efficacy of indigenous forces in counterinsurgency: Lessons from Chechnya and Dagestan. (3rd May 2016) - Aslan Souleimanov, Emil; Aliyev, Huseyn
Abstract: This study seeks to identify factors conducive to the (in)efficacy of indigenous forces (IF) in counterinsurgency (COIN) operations in Russia's republics of Chechnya and Dagestan. Empirically, it is the first study to offer an examination of the deployment of IF in the North Caucasus-based COIN. The findings of this article emphasize that the effectiveness of COIN in Chechnya, unlike Dagestan, is conditioned by a number of factors pertaining to the structural and organizational characteristics of IF. Of these, the IF's experience as former insurgents, their access to insider information, and their loyalty to incumbents – often maintained by the threat of collective punishment – have proven decisive for a relatively successful COIN in Chechnya.